2017
DOI: 10.1089/dia.2017.0035
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Glucose Monitoring: A Review of Recent Studies Demonstrating Improved Glycemic Outcomes

Abstract: Continuous Glucose Monitoring (CGM) has been demonstrated to be clinically valuable, reducing risks of hypoglycemia and hyperglycemia, glycemic variability (GV), and improving patient quality of life for a wide range of patient populations and clinical indications. Use of CGM can help reduce HbA1c and mean glucose. One CGM device, with accuracy (%MARD) of approximately 10%, has recently been approved for selfadjustment of insulin dosages (nonadjuvant use) and approved for reimbursement for therapeutic use in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
267
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 357 publications
(293 citation statements)
references
References 136 publications
(190 reference statements)
5
267
2
3
Order By: Relevance
“…However, there is a time lag between subcutaneous glucose and capillary BG concentrations due to the transport of glucose from the vascular to the interstitial space resulting in a difference in measured glucose level [15, 16]. CGM systems have been shown to improve glycaemic control and HbA1c, and to reduce the risk of hypoglycaemia [17]. However, CGM is expensive and not widely available due to limited reimbursement [18].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a time lag between subcutaneous glucose and capillary BG concentrations due to the transport of glucose from the vascular to the interstitial space resulting in a difference in measured glucose level [15, 16]. CGM systems have been shown to improve glycaemic control and HbA1c, and to reduce the risk of hypoglycaemia [17]. However, CGM is expensive and not widely available due to limited reimbursement [18].…”
Section: Introductionmentioning
confidence: 99%
“…33 Last but not least, flash glucose monitoring data may become available as ''continuous'' like CGMs and by using Bluetooth technology, data could be made available on the pumps or smart phones and possibly be used to drive insulin delivery like in the artificial pancreas. 32,34,35 We thank Abbott Diabetes Care for thinking ''outside the box'' and launching the first no calibration (factory calibrated) 14-day on-demand sensor. The science behind the factory calibration of flash glucose monitoring was discussed in detail by Hoss et al in this supplement.…”
mentioning
confidence: 99%
“…It reflects in a much better way intra-and interday glycemic excursions that may lead to acute events (such as hypoglycemia) or postprandial hyperglycemia, which have been linked to both microvascular and macrovascular complications (28). Additionally and beyond the effects of the meta-analysis of Zhu et al (29), Rodbard (30) reported that CGM has been demonstrated to be useful in reducing the risks of hypo-and hyperglycemia too, improving glycemic variability and increasing patients' quality of life in both type 1 and type 2 diabetes (30). Additionally and beyond the effects of the meta-analysis of Zhu et al (29), Rodbard (30) reported that CGM has been demonstrated to be useful in reducing the risks of hypo-and hyperglycemia too, improving glycemic variability and increasing patients' quality of life in both type 1 and type 2 diabetes (30).…”
Section: Glucose Monitoringmentioning
confidence: 99%